Vibrations in centrifugal pumps induced by pressure pulsations with blade frequency - Karaśkiewicz, Krzysztof (Instal, 2024)
A common cause of vibration in centrifugal pumps is pressure pulsations resulting from the interaction between the impeller and the vaned diffuser. These pulsations are periodic and can propagate to the impeller discs, potentially causing damage. An effective tool for determining the set of blade-passing frequencies that characterize these pulsations is an encounter diagram. Pressure pulsations may induce structural resonance related to the natural frequencies of the pump components or acoustic resonance within the piping components. Understanding the bladepassing frequencies facilitates the diagnosis of centrifugal pump vibrations. Pressure pulsations can be mitigated by trimming the impeller or by skewing the edges of the impeller blades or diffuser vanes.